THE USE OF MEANINGFUL COMMUNICATION BARRIER FOR INTERPRETING EDUCATIONAL INFORMATION BASIS OF THE EFFECT OF THE LEXICAL CHARACTERISTICS OF THE SUBJECT - Alexander А. Isaev; Tatiana М. Plekhanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes the structure and especially the impact on the participants of the communication process of the meaningful communication barrier. The elements of the process of business and friendly relations are identified and discussed from the point of view of psychology. The assumption is made that the trust and its parameters are the basis for effective communication. As parameters the sources of trust/not trust to the opponent are selected. The essence of the author's technology is not only a systematic approach to the allocation of substantial elements of the barrier, but in the emergence of the confidence parameters found in the existing barrier. The meaningful barrier was previously perceived as "filter" information. Now, finding additional elements and combining them into a single system, the author argues that the substantial barrier performs the function of interpretation of information, as received and sent. A barrier is a set of parameters that interpret and form the learned unit of the message. Later these parameters are combined into a whole message that is transmitted by the subject of communication to the object. The testing of the proposed technology was conducted at the Department of Humanities education SamSTU by processing lecture material. To check the viability of the proposed technology among students of different specialties (technical and humanitarian) SamSTU experiment was conducted. The